EFFICACY, SAFETY, AND COST-EFFECTIVENESS OF TELMISARTAN AND CILNIDIPINE IN HYPERTENSIVE PATIENTS WITH CORONARY ARTERY DISEASE IN A TERTIARY CARE TEACHING HOSPITAL: A PROSPECTIVE COMPARATIVE STUDY - ALTHAB BEGUM MOHAMED,; SATYAJIT MOHAPATRA,; JERIN JAMES,; JANANI L, (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The objective of the study is to evaluate and compare telmisartan with cilnidipine’s cost-efficiency, safety, and effectiveness in hypertensive patients with coronary artery disease (CAD). Methods: From January 2017 to June 2018, a non-randomized, open-labeled, comparative study was carried out in the SRM Medical College Hospital’s Department of Cardiology. A total of 126 individuals with electrocardiogram-confirmed CAD and hypertension were divided into two groups, each consisting of 63 participants: Telmisartan (40 mg) and cilnidipine (10 mg). Blood pressure, renal function, electrolytes, adverse effects, and costs were measured at baseline, 12 weeks, and 24 weeks. Results: At both 12 and 24 weeks, telmisartan reduced systolic blood pressure more than the other medication (mean difference at 24 weeks: 5.6 mmHg; p<0.000). Both drugs showed comparable diastolic blood pressure reductions. Although cilnidipine caused a significant drop in serum creatinine (p=0.001), renal parameters stayed constant. Telmisartan was better tolerated than cilnidipine, which had more side effects. The cost-effectiveness of cilnidipine was significantly higher (mean cost difference: Indian rupee 96.8; p<0.000). Conclusion: Both drugs are effective antihypertensives for people with CAD. While cilnidipine is more affordable, telmisartan provides better blood pressure control and renal safety with acceptable tolerability.